Circular photogalvanic effect from third-order nonlinear effect in 1T'-MoTe2. (28th January 2021) - Ma, Junchao; Muniz, Rodrigo A.; Qi, Shaomian; Lai, Jiawei; Zhang, Kenan; Liu, Yinan; Zhuo, Xiao; Chen, Shuxia; Chen, Jian-Hao; Zhou, Shuyun; Sun, Dong
Abstract: The two-dimensional layered material MoTe2 has aroused extensive research interests in its rich optoelectronic properties in various phases. One property of particular interest is the circular photogalvanic effect (CPGE): a conventional second order nonlinear optical effect that is related to the chirality of materials. It has been demonstrated in Td -MoTe2, a type-II topological Weyl semimetal candidate, while it has been unclear so far whether it exists in the semimetallic 1T' phase, another interesting phase that hosts a quantum spin hall state. In this article, we report a clear experimental observation of in-plane CPGE in 1T'-MoTe2 . The observation is confirmed under various experimental designs with excitation by normally incident mid-infrared laser, and we find it to be related to an in-plane internal DC electric field. We attribute the circular photogalvanic response to a third-order nonlinear optical effect involving this DC electric field, which is consistent with the crystal symmetry of the lattices and present in both the 1T' and Td phases of the material.